Mesostigmatic mites (Acari: Mesostigmata) of Saudi Arabia (excluding Phytoseioidea), new records and a key to the known species - Alatawi, Fahad Jaber; Kamran, Muhammad; Mirza, Jawwad Hassan (Zootaxa, 2018)
This paper reports on 35 species and 33 genera belonging to 18 families of the order Mesostigmata, collected from different provinces of Saudi Arabia. Among these, eight families, 21 genera and 30 species, mostly collected from date palm agroecosystem, are new to the fauna of Saudi Arabia. Five species reported previously are also recorded in this study. The collection data and distribution of all species recorded in this study as well as those reported previously are given. A comprehensive key to the females of the mesostigmatic mites reported from Saudi Arabia, except the Phytoseioidea, is provided.